Comparative study of photo-produced ionosphere in the close environment of comets - Beth,A; Galand,M; Heritier,K (Astronomy & Astrophysics, 2019)
Context. The Giotto and Rosetta missions gave us the unique opportunity of probing the close environment of cometary ionospheres of 1P/Halley (1P) and 67P/Churyumov-Gerasimenko (67P). The plasma conditions encountered at these two comets were very different from each other, which mainly stem from the different heliocentric distances, which drive photoionization rates, and from the outgassing activities, which drive the neutral densities.Aims. We asses the relative contribution of different plasma processes that are ongoing in the inner coma: photoionization, transport, photoabsorption, and electron–ion dissociative recombination. The main goal is to identify which processes are at play to then quantitatively assess the ionospheric density.Methods. We provide a set of analytical formulas to describe the ionospheric number density profile for cometary environments that take into account some of these processes. We discuss the validity of each model in the context of the Rosetta and Giotto missions.Results. We show that transport is the dominant loss process at large cometocentric distances and low outgassing rates. Chemical plasma loss through e−-ion dissociative recombination matters around 67P near perihelion and at 1P during the Giotto flyby: its effects increase as the heliocentric distance decreases, that is, at higher outgassing activity and higher photoionization frequency. Photoabsorption is of importance for outgassing rates higher than 1028 s−1 and only close to the cometary nucleus, well below the location of both spacecraft. Finally, regardless of the processes we considered, the ion number density profile always follows a 1r law at large cometocentric distances.